2023
DOI: 10.3389/fvets.2023.1075308
|View full text |Cite
|
Sign up to set email alerts
|

Risk perceptions of avian influenza among poultry farmers on smallholder farms along border areas of Thailand

Abstract: IntroductionThailand has not reported any cases of avian influenza since 2008. However, avian influenza viruses circulating in poultry in neighboring countries may have potential for transmission to humans. The aim of this study was to assess risk perceptions of poultry farmers and traders in three border provinces of Thailand adjacent to Laos.Materials and methodsPoultry farmers and traders were interviewed in-person during October–December 2021 by health and livestock officials using a standardized questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Finally, we holistically analyzed the network at the subdistrict level to describe the poultry trade patterns in the study area. A better insight into the demographic characteristics of the participants involved was previously addressed in our previous study ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we holistically analyzed the network at the subdistrict level to describe the poultry trade patterns in the study area. A better insight into the demographic characteristics of the participants involved was previously addressed in our previous study ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…An additional study on the impacts of socioeconomic factors on poultry trade may provide insights into this aspect of the trade network. Indeed, we used our questionnaire results to investigate the impact of certain socioeconomic factors on risk perception in one of our prior studies ( 40 ). However, there was still some long-distance poultry trade, and our findings were consistent with previous studies on livestock movements in Thailand, which showed that most of the movements were managed locally with some remote translocations ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Effective biosecurity farming practices hinge not only on the implementation of established management protocols but also on the farmers' awareness of the consequences of improper behaviors on pathogens’ introduction and transmission to domestic birds ( Hinjoy et al, 2023 ). The utilization of visual evidence depicting wild birds around poultry houses, such as the footages recorded through camera traps, could facilitate health authorities in educating and raising awareness between stakeholders regarding wild bird presence and potential pathogen spillover opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy will require the participation of several countries in order to mount effective regional surveillance for emerging diseases, with leadership by key people within the countries [ 25 ]. It is essential that the issues be seen from the viewpoint of animal owners as well as decision makers, since this is likely to influence their willingness to become involved and to act on information [ [188] , [189] , [190] ].…”
Section: Building the Pathway For Participating Asian Countriesmentioning
confidence: 99%